Endothelial dysfunction in patients with rheumatoid arthritis and comorbidity - A. K. Knyazeva; E. B. Komarova; N. G. Bludova (Современная ревматология, 2018)
Rheumatoid arthritis (RA) and subclinical hypothyroidism (SHT) have close pathogenetic relationships, the synergism of which worsens the clinical course and increases the risk of visceral complications. Objective: to study the ultrasound parameters of endothelial dysfunction (ED) in patients with RA concurrent with SHT. Patients and methods: 139 patients with RA were divided into two groups: 1) 48 patients with RA; 2) 91 patients with RA concurrent with SHT. The ultrasound parameters of endothelial regulation of vascular tone were determined by intravascular ultrasonography using an ESAOTE MyLAB40 apparatus in accordance with the international guideline. Results and discussion. The study of endothelial regulation of vascular tone established that all the examinees with RA had ED that increased with the higher degree of activity and longer duration of RA. Patients with RA in the presence of SHT had more significant abnormalities in the ultrasound parameters of endothelial regulation of vascular tone and in the degree of ED, which increased with the longer duration and higher activity of the disease. The early detection and correction of comorbidity in patients with RA will reduce cardiovascular risk and improve quality of life.